Blood pressure target for hypertension in chronic kidney disease: One size does not fit all. Issue 5 (3rd May 2020) - Kollias, Anastasios; Kyriakoulis, Konstantinos G.; Stergiou, George S.
Abstract: There is disagreement between the American and the European guidelines for hypertension management in regard to the optimal blood pressure target in patients with chronic kidney disease (CKD). Randomized clinical trials and meta‐analyses of individual patient data pooled from these trials do not clearly support an intensive blood pressure target for the entire population of CKD patients with hypertension. However, some evidence suggests that in CKD patients with proteinuria strict blood pressure control might confer benefit in terms of renal outcome. Tailored treatment strategy based on the individual's proteinuric profile and tolerability along with standardization of blood pressure measurement methodology including out‐of‐office evaluation are of paramount importance in patients with CKD.